Brain response to food odors is not associated with body mass index and obesity-related metabolic health measures. (1st January 2022) - Poessel, Maria; Morys, Filip; Breuer, Nora; Villringer, Arno; Hummel, Thomas; Horstmann, Annette
Abstract: Smell perception plays a role in eating behavior and might be involved in the development of obesity. In fact, olfactory function is impaired in obesity and might depend on metabolic health factors. To date, the underlying neural mechanisms remain unclear. Here, we investigate neural processing of food-related odors in normal-weight, overweight and obese individuals. Fifty-three young and healthy participants (28.8 ± 4.4 years, 27 female; 24 normal-weight, 10 overweight, and 19 obese) were presented with high- (chocolate, potato chips) and low-caloric (orange, cucumber) food odors during a functional magnetic resonance imaging (fMRI). We also assessed olfactory identification ability, body mass index (BMI), body fat percentage, insulin resistance, and leptin levels. In brief, olfactory perception of food odors was linked to brain activity in the entorhinal and piriform cortex, and the insula, hippocampus, and amygdala. Insulin resistance was negatively related to olfactory identification. Additionally, perception of sweet versus savory odors was related to a higher brain activity in the right middle/superior frontal gyrus. Finally, we found no effect of obesity status, BMI, metabolic factors, or body fat percentage on neural responses to food odors. Overall, this suggests that food odor processing might depend on factors other than body weight status or associated markers of metabolic health.